ERITROPOITIN FISIOLOGI, ASPEK KLINIK, DAN LABORATORIK - P B Notopoero (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2007)
Erythropoietin is a glycoprotein hormone produced by kidney and functioning as regulator for eryhtropoietic processes. The regulation of erythropoietic processes are stimulation of proliferation, maturation erythroid progenitor cells and prevention of apoptotic process.The balance between dinamic erythropoietic processes and loss of erythrocytes is regulated by homeostatic mechanism. The decrementof EPO production will cause anemia such as anemia in end state renal disease. The development of rHuEPO support the invention ofsensitive and specific immunoassay methods to measure the level of EPO. There are various commercial kit using various immunoassaymethods used to achieve this purpose. The use of rHuEPO gives dramatic impact for the improvement of end state renal disease patients’squality of life. The research for the effect of EPO in the neuron, vascular, and retinous tissue develop the use of EPO for the neurology,cardiology and opthalmology area. This should be followed with the understanding of the patophysiology of EPO effect in the variousorgans. In 1990. the rHuEPO is used to replace the blood transfusion as the blood doping. The various direct and indirect methods candetect the missuse of rHuEPO as doping in the world sport events.